Ginsenoside Rg3 and Rh2 protect trimethyltin‐induced neurotoxicity via prevention on neuronal apoptosis and neuroinflammation. (2nd October 2018) - Hou, Jingang; Xue, Jianjie; Wang, Zi; Li, Wei
Abstract : The acute exposure of trimethyltin (TMT) develops clinical syndrome characterized by amnesia, aggressive behavior, and complex seizures. This neurotoxicant selectively induces hippocampal neuronal injury and glial activation accompanied with resultant neuroinflammation. Here we report two candidates ginsenosides Rg3 and Rh2 as neuroprotection agents using a mouse model of TMT intoxication via a single injection (2 mg/kg) and primary neuronal culture systems. Four‐week administration of Rg3 or Rh2 significantly reduced TMT‐induced seizures and behavioral changes. Rg3 and Rh2 significantly attenuated the oxidative stress evidenced by improvement on antioxidant enzymes and neuronal loss and astrocytic activation in mouse brain. In primary cultures, TMT induced significant neuronal death after 24‐h intoxication and vigorous secretion of inflammatory cytokines (IL‐1α/β, IL‐6, TNF‐α, and MCP‐1) in astrocytes. Pretreatment with Rg3 or Rh2 not only reduced cell death but efficiently suppressed above mentioned inflammatory cytokines confirmed by antibody array test. The underlying protective mechanism by Rg3 and Rh2 was delineated through selective upregulation of PI3K/Akt and suppression of ERK activation. Intriguingly, Rg3 and Rh2 protected oligodendrocyte progenitor cells (O‐2A) from TMT intoxication via promoting type 2 astrocytic differentiation without further inflammatory activation. Collectively, Rg3 and Rh2 interventions aimed at reducing oxidative stress and neuroinflammation neurotoxicity therefore are of therapeutic benefit in TMT‐induced neurodegeneration.